Oxidation behaviour of glass–quartz and glass–quartz–aluminium composite coatings on Ti–6Al–4V alloy. (April 2015) - Xiao, Z.; Tan, F.; Wang, W.; Lu, H.; Cai, Y.; Qiu, X.; Chen, J.; Qiao, X.
Abstract : Glass–quartz and glass–quartz–aluminium composite coatings were successfully produced on Ti–6Al–4V alloy by slurry method. The oxidation behaviour of the specimens at 800°C for 100 h was studied. Both composite coatings exhibited good high temperature oxidation resistance. After oxidation for 100 h, quartz and diopside were main crystalline phases in the glass–quartz composite coating. Some open pores appeared on the surface of the glass–quartz composite coating, which might be related to the intensive crystallisation of diopside in the composite coating. While in the glass–quartz–aluminium composite coating, no open pores could be seen, and some new phases such as silicon and alumina were observed. The silicon and alumina phases might be originated from the reaction between glass and molten aluminium. Because of this, incorporation of aluminium particles into the composite coating slows the nucleation and growth rate of diopside.